Event Marketing and Public Relations - Reba Ellen Hicks; Ricky Telg; Tracy Irani (EDIS, 2013)
Marketing your event so that people know about it and are motivated to attend is extremely important. The five P’s of marketing – product, promotion, price, place (location), and public relations – must be taken into consideration in order to have an event that is well attended. This 2-page fact sheet was written by Reba Ellen Hicks, Ricky Telg, and Tracy Irani, and published by the UF Department of Agricultural Education and Communication, July 2013.